Law on Economical and Efficient Use of Energy - The Nationnal Assembly (2010)
This Law provides economical and efficient use of energy; policies and measures to promote economical and efficient use of energy; and the rights, obligations and responsibilities of organizations, households and individuals in economical and efficient use of energy.